Biosensing and Bioimaging Trends and Perspective - Wang, Xuemei; Jiang, Hui (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Biosensing and bioimaging techniques largely promote the accurate diagnosis of intractable diseases, such as cancers, on the basis of specific molecular targets, or as-called biomarkers. To realize the assays with ultrahigh sensitivity and selectivity, the wide application of molecular biology and nanotechnology are of great necessity. Both directions may offer effective signal amplification strategies, as well as inhibition of cross-reaction interference. Therefore, this Special Issue, "Biosensing and Bioimaging: Trends and Perspective", highlights the recent developments in intelligent biomolecule/nanostructure-based probes for bioimaging and biosensing applications. It consists of five peer-reviewed papers that cover current hot topics, such as biodegradable materials, DNA assembly, shRNA delivery and chimeric proteins, which will provide a unique perspective of advanced biosensing and bioimaging techniques.